Peranan BUMN dalam Pelaksanaan Tanggung Jawab Sosial Perusahaan untuk Meningkatkan Kesejahteraan Rakyat - Yeti Sumiyati (Jurnal Hukum IUS QUIA IUSTUM, 2013)
The problems studied in this research are: First, the role of State-Owned Enterprises (SOEs) in producing high quality goods/service through the SOE management and control based on the GCG principles; second, the role of SOEs in promoting the small scale industries/cooperatives development through Corporate Social Responsibility (CSR). The method used in this research is normative juridical. This research finds and concludes that: First, in any aspects, the implementation of SOE roles is still far from ideal as stipulated in the Article 33 of Constitution 1945, which should be beneficial for the prosperity and welfare of the community. In fact, the SOEs have already implemented the GCG principles in their management and control as the effort to optimize the role of SOEs. Second, the role of SOEs to promote the development of the farmers’ small scale industries/cooperatives through the implementation of CSR can at least help create the independence economic of the farmers as long as the implementation is sustainable and involve the participation of all farmer community.